ESTIMATION OF GENE EFFECTS BASED ON JOINT SCALING TEST AND MODEL FIT SCHEME FOR QUANTITATIVE TRAITS IN MELON - BIKRAMJIT SINGH; VINOD KUMAR VASHISHT; SAYEED ABDULHAMID PATEL (The Bioscan, 2015)
The study comprised of six basic generations viz., P1 , P 2 , F 1 , F 2 , B 1 and B 2 of cross Punjab Sunehri × KP 4 HM-15 (cross-I) and Punjab Sunehri × IC-267379 (cross-II). Scaling tests indicated epistasis for most of the traits. The results inferred additive gene effect (D) was lower than dominance gene effect (H) for most of the traits except days to first fruit ripening (DFF) (D= 1.46±0.31**; H= -2.69±0.79**) while rind thickness (RT) was non- significant in cross-I and DFF, fruit weight, flesh thickness (FT), RT and fruit cavity in cross-II. Duplicate epistasis was recorded for most of the traits. Variance analysis showed that additive genetic variance (ó 2 D) was predominant for all traits in both crosses. Degree of dominance was >1 for DFF (1.12), fruit weight (1.45), fruit yield/vine (1.42) and polar (3.32) and equatorial diameter (7.48) in cross-I; for equatorial diameter (1.34) and FT (1.06) in cross-II. Moderate heritability was recorded for all traits except days to open first pistillate flower (84.30%), DFF (87.16%) and polar diameter (92.01%) in cross-I and equatorial diameter (89.07%) and FT (89.96%) in cross-II while genetic gain was found to be more for fruit number/vine (9.51%), RT (9.09%) and TSS (7.90%) in cross- I and FT (59.09%), RT (23.07%) and fruit number/vine (9.20%) in cross-II.